Indian shoes eaudiobook - Smith, Cynthia Leitich (Heartdrum, 2022)
The beloved chapter book by New York Times bestselling author Cynthia Leitich Smith about the love and adventures shared by a Cherokee-Seminole boy and his Grampa! A perfect pick for new readers. What do Indian shoes look like, anyway? Like beautiful beaded moccasins... or hightops with bright orange shoelaces? Ray Halfmoon prefers hightops, but he gladly trades them for a nice pair of moccasins for his grampa. After all, it's Grampa Halfmoon who's always there to help Ray get in and out of scrapes—like the time they teamed up to pet sit for the whole block during a holiday blizzard! Award-winning author Cynthia Leitich Smith writes with wit and candor about a boy and his grandfather, sharing all their love, joy, and humor. In partnership with We Need Diverse Books